Fixation of Condyle with Delta Plate: A Case Report - Santosh Kumar Subudhi1 , Sthitaprajna Lenka1 , Sanchari Sinha Roy2 , Waseem M. Alam2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Condyle fractures account for 25-35% of mandibular fractures and deserve special care from the rest of themandible due to their anatomical distinctions and capacity for healing. Past clinical and biomechanical trialshave suggested the use of two miniplates for condyle fracture fixation. Two miniplates allow the proximalcondyle fragment to a certain scale, and thus are useful in low fractures. This present case report shows theuse of delta-shaped mini plates (titanium) in ORIF of subcondylar fracture.